Artificial intelligence IV : methodology, system, application - International Conference on Artificial Intelligence: Methodology, Systems, Applications (4th : 1990 : Albania, Bulgaria); Jorrand, Ph; Sgurev, Vasil (Netherlands : Elsevier, 1990)
39